Dawn of the planet of the apes [videorecording (DVD)] - Serkis, Andy; Oldman, Gary; Clarke, Jason, 1969-; Russell, Keri, 1976- (Twentieth Century Fox Home Entertainment, LLC, 2014)
A growing nation of genetically evolved apes led by Caesar is threatened by a band of human survivors of the devastating virus unleashed a decade earlier. They reach a fragile peace, but it proves short-lived, as both sides are brought to the brink of a war that will determine who will emerge as Earth's dominant species.